2014
DOI: 10.7860/jcdr/2014/7817.4001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lipoprotein(a) and Thyroid Hormones in Hypothyroid Patients

Abstract: Background and Objective: Changes in plasma lipid con cen trations are well known metabolic consequences of thyroid dysfunction. The alterations are most prominent in hypothyroidism which is typically associated with pronounced hypercholesterolaemia and frequently with moderate hyper triglyceridaemia. In cases of hypothyroidism, how the serum Lp(a) levels are influenced by thyroid hormone remains unknown and contradictory results on the effect of thyroid hormone on serum Lp(a) levels have been reported. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
3
7
1
1
Order By: Relevance
“…With respect to the parameters of age (20,21) gender (22), and etiology of thyroid disease (23,24), the present study sample is consistent with previous studies of thyroid disease. The average age reported in indivi duals Figure 1.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With respect to the parameters of age (20,21) gender (22), and etiology of thyroid disease (23,24), the present study sample is consistent with previous studies of thyroid disease. The average age reported in indivi duals Figure 1.…”
Section: Discussionsupporting
confidence: 88%
“…In a separate study, Kaliaperumal and cols. (21) found that patients with untreated hypothyroidism had a mean cholesterol level (232.12 ± 5.12 mg/dL) significantly higher than the control group (169.65 ± 2.59 mg/dL). A third study showed that individuals with TSH levels < 0.1 mIU/ml had a mean cholesterol level of 181.70 mg/dL, whereas individuals with TSH levels > 10 mIU/ml had a mean cholesterol level of 209.15 mg/dL (15).…”
Section: Alanine Aminotransferase In Thyroid Diseasesmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the complications with the hormones secreting organ affect the fatty tissue and steroidogenic tissues. Due to the fact that lipid metabolism remains the most effective energy-supplying source for the organism, even slight alternations in thyroid hormones levels severely affect the plasma lipoproteins [26,[28][29][30]. The patients who supplied the thyroid hormones exhibited lower LDL and higher triglycerides levels comparing to the non-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that a high level of saturated fatty acids leads to an increase in proinflammatory cytokines, activates Toll-like receptors and influences the development of the oxygenase metabolism of polyene FA [8]. M. Peppa and other researchers have investigated that in half of patients with hypothyroidism, a lipid metabolism disorder is observed [2,9,10].…”
mentioning
confidence: 99%